The risks of smart cities and the perspectives of their management based on corporate social responsibility in the interests of sustainable development - Irina A. Morozova; Stanislav S. Yatsechko (Risks, 2022)
Purpose: Bring to light the risks of smart cities and the perspectives of their management. It has been discovered that smart cities are created and developed under the impact of not only technological factors but also social factors. The connection between smart cities and quality of life is systemic (direct and reverse)-the quality of life also specifies the creation and development of smart cities. The impact of the COVID-19 pandemic on the development of smart cities is almost null (smart cities do not depend on the implementation of SDG 3). This paper's originality lies in the description of a new angle of studying smart cities-from the position of risks, and in the determination of the current level of these risks and the dynamics of their change during systematisation and description of the wide international experience of creation and development of smart cities. This paper's uniqueness lies in the development of a new approach to managing the creation and development of smart cities, which is based on corporate social responsibility, thus specifying and ensuring the involvement and important role of the subjects of entrepreneurship in this process. It is proved that the contribution of smart cities to the implementation of the SDGs is much wider and goes beyond the limits of SDG 9-it also extends to SDG 1 and SDGs 11-13.
Keywords: 330; risks; smart cities; corporate social responsibility; sustainable development; SDGs; risk management